Proceedings of the 2016 5th International Conference on Environment, Materials, Chemistry and Power Electronics 2016
DOI: 10.2991/emcpe-16.2016.70
|View full text |Cite
|
Sign up to set email alerts
|

Effect of citric acid on toxicity of graphene towards freshwater algae (Chlorella pyrenoidosa)

Abstract: Abstract. With the increasing in production and application, graphene will inevitable be released into the aquatic environment and have impacts on aquatic organisms. In this work, we investigated the toxicity of graphene to algal cells (Chlorella pyrenoidosa) in the presence of dissolved organic matter. The results showed that the toxicity of graphene is concentration dependent, and the median effective concentration (EC 50 ) at 96 h was 41.35 mg/L. In addition, the toxicity was significantly reduced by citric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The data obtained can be explained by the fact that the use of citric acid in working concentrations goes beyond the boundaries of the chlorella optimum zone. In other studies, it was shown that citric acid plays the role of a protector (at concentrations of 5, 10, 20 mg/l) during the action of graphene on the Chlorella pyrenoidesa cell culture [27]. The role of citric acid in the protection of higher plants during copper intoxication was also noted [28].…”
Section: Resultsmentioning
confidence: 87%
“…The data obtained can be explained by the fact that the use of citric acid in working concentrations goes beyond the boundaries of the chlorella optimum zone. In other studies, it was shown that citric acid plays the role of a protector (at concentrations of 5, 10, 20 mg/l) during the action of graphene on the Chlorella pyrenoidesa cell culture [27]. The role of citric acid in the protection of higher plants during copper intoxication was also noted [28].…”
Section: Resultsmentioning
confidence: 87%
“…Wang et al (2016) also reported that graphene inhibited growth in Scenedesmus obliquus in a concentrationdependent manner. Guo et al (2016) observed dose-dependent toxicity of graphene in another species, Chlorella pyrenoidosa.…”
Section: Introductionmentioning
confidence: 90%